IN SILICO DOCKING ANALYSIS OF BIOACTIVE COMPOUNDS FROM CALOPHYLLUM INOPHYLLUM L. ETHANOL LEAF EXTRACT AGAINST EGFR PROTEIN - K, Jaikumar; Noor Mohamed, Sheik; W, John Wyson; M, Deventhiran; A, Babu; D, Anand; P, Saravanan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of this study was to evaluate the effective new phytocomponents from Calophyllum inophyllum ethanol leaf extract against breast cancer target protein of Epidermal Growth Factor Receptor (EGFR) using in silico docking studies. Materials and Methods: The identification of compounds was done by GC-MS analysis. The in silico docking studies were carried out using Discovery Studio 4.0 software. Results: The GC-MS analysis of ethanol leaf extract revealed the presence of eleven compounds. The docking analysis have exhibited moderate to potent inhibition with a range of dock score 3 to 55. 2H-Benzo(cd) pyrene-2,6(1,H)-dione, 3,5,7,10-tetrahydroxy-compound showed the dock score of 55.427. Conclusion: The results revealed out that the compounds present in Calophyllum inophyllum can inhibit the EGFR protein. The plant possesses anticancer potential because of the various bioactive compounds presence which is mainly responsible for anticancer activity. Â